Increased CD4(+)CD16(+) and CD4(+)CD56(+) T cell subsets in Behcet's disease - DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (SPRINGER VERLAG, 1999)
Behcet's disease is a systemic vasculitis of unknown etiology. Various immune abnormalities have previously been shown in Behcet's disease. We investigated T lymphocyte subsets associated with cytotoxic activity and natural killer (NK) cells by flow cytometry in 37 patients with Behcet's disease, 38 healthy controls, and 17 diseased control patients. Compared to the healthy controls, CD4(+)CD16(+) and CD4(+)CD56(+) subsets were found to be higher in the Behcet's disease group as well as in the disease control group (CD4(+)CD16(+): B = 5 +/- 3, DC = 14 +/- 14, HC = 3 +/- 2, P = 0.001; CD4(+)CD56(+): ED = 11 +/- 5, DC = 18 +/- 17, HC = 8 +/- 6, P = 0.01). CD8(+)CD16(+) and CD8(+)CD56(+) T cell subsets were at normal levels in Behcet's disease but found to be elevated in disease controls. Similarly, NK cells (CD16(+)CD56(+)) were high only in the disease control group. Significant increases in CD4(+)CD16(+) and CD4(+)CD56(+) cell subsets in Behcet's patients and disease controls suggest that T cell activation patterns of these subsets in Behcet's disease are similar to those in other inflammatory disorders.
Keywords: Behcet's disease; cytotoxic T cells; CD16(+)CD56(+); LYMPHOCYTES; PHENOTYPE; PROFILE; NUMBERS